Analisis Pengaruh Inflasi, Investasi Syariah, Nilai Tukar dan Pembiayaan Syariah Terhadap Pertumbuhan Ekonomi - Firda Sari, Lailisa; Pebruary, Silviana (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
This study aims to analyse the effect of Inflation, Islamic Investment, Exchange Rates, and Islamic Financing on Economic Growth in Indonesia. This study uses monthly secondary data from 2012 to 2023 which is analysed using the Vector Error Correction Model (VECM) method. The results of the analysis show that inflation has a significant negative effect on economic growth in the long term and short term. Islamic investment affects economic growth in the long term positively and significantly, while in the short term it affects economic growth positively and insignificantly. The exchange rate has a significant negative effect in the short term and in the long term the exchange rate has a positive and insignificant effect on economic growth. Islamic financing has a significant negative effect in the long term and an insignificant negative effect in the short term. This research is expected to help policy makers, government and academics to stabilise the macroeconomy, strengthen the Islamic financial sector and increase the synergy between Islamic financing and the real sector in supporting sustainable economic growth.